Estudo da formação de fase vítrea no sistema Fe-Mo-P-C-B utilizando cálculos termodinâmicos e critério de amorfização - Martins, Droanna Rosa (Universidade Federal de São Carlos, 2022)
Glasses with high atomic concentration of iron have been studied due to its magnetic properties, high mechanical and corrosion resistance, and low cost of the raw material. However, these materials present low glass-forming ability phase formation and low plastic deformation capability, which make them difficult to produce and with limited application. The objective of the present study is to use the the criterion (λmin + ∆ℎ) to investigate the glass-forming ability of glassy phase of the Fe-Mo-P-C-B system and associate it to the results of thermodynamics calculations to understand the formation of primary phase and liquidus temperature of alloys. The criterion of glassy phase formation (λmin + ∆ℎ) was applied to composition of alloys with a total percentage of metalloid elements from 17 to 25% at.. All the possible concurrent phases of the glassy phase were found in literature. All the binary, ternary, quaternary, and quinary possibilities were considered. The alloys selected from the criterion of glassy phase formation were better investigated by using the CALPHAD method by the software Pandat. During the selection of the compositions, the minimum Fe atomic concentration considered was at 60%. The increase of the percentage of metalloids in the Fe-Mo-P-C-B system raises the capability of glassy phase formation of the alloy. From a metalloid atomic percentage of 23% the capability of formation of glassy phase doesn't change significantly. No investigated composition had a phase with ductile character as primary phase. The liquidus temperature of the alloys is lowered with the increase of the percentage of metalloids, and decreases even more to higher Fe concentration. Based in the results of the criterion used in the present study, the capability of glass phase formation, liquidus temperature, and the phases formation, three alloys from the Fe-Mo-P-C-B system presented to be promising to be experimentally investigated: Fe77Mo6P8C7.5B1.5 (17% metalloid), Fe77Mo5P9C7.5B1.5 (18% metalloid), Fe77Mo3P11C7.5B1.5 (20% metalloid).
Study of the glass-forming ability of Fe-Mo-P-C-B using thermodynamic calculations and an amorphization criterion
Keywords: Ligas formadoras de fase vítrea à base de Fe; Critérios de formação de fase vítrea; Cálculos termodinâmicos; Fe-based bulk metallic glasses; Glass phase formation criterion; Thermodynamic calculation; ENGENHARIAS::ENGENHARIA DE MATERIAIS E METALURGICA::METALURGIA FISICA